Evaluating the Impact of Multidisciplinary Nursing Teams on Healthcare Quality in Primary Care Settings - Abdulaziz Falah Alrasheedi; Asma Jamel Alanezi; Faisal Mohammed Alanazi; Khlood Hamdan Al Blwei; Atheer Hamdan Al Blwei; Norah Ghannam Ghanem Alshammary; Najah Ghannam Ghanem Alshammary; Manal Nazal Alenezi (International Journal of Medical Toxicology and Legal Medicine, 2024)
The multidisciplinary nursing teams play a significant role in the primary setting for care provision. It ensures that such care is holistic, meeting patient-centered needs by actualizing various skills offered by different health professionals. Whereas such teams are generally performing well, there are sustained disparities in communication and confusion over the professional role; this calls for a great need for the definition of roles and enhanced training. The presentation will review benefits, dynamics, and challenges related to multidisciplinary nursing teams in primary care, as well as strategies to optimize their integration in support of better patient outcomes.